Exploring Factors that Encourage and Obstruct Change in Management Accounting in a Company - Lutfi Ayu Fadhilah Utami; Ira Lestari; Khikmatul Marfuah (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2024)
The purpose of this study was to determine the factors driving and inhibiting management accounting changes in a company. The research conducted by researchers used a descriptive qualitative approach method with field research. The subjects in this study are companies with management accounting update methods and those that have not experienced management accounting updates. The results of the study concluded that changes in management accounting occur due to many factors, one of which is changes included in the organizational environment and external factors. These changes include things that involve the process of planning, controlling, and decision making in a company. Factors that can drive management accounting changes in a company include technological changes, market developments, competition, regulations, and internal company factors such as leadership changes and organizational restructuring. Management accounting changes can also be influenced by organizational factors such as cooperation, takeovers, and agency relationships. In addition, factors that can hinder management accounting changes in a company are staff, organizational changes, costs, profitability, data quality, intensive, and agency.